Paraoxonase 1, HDL Subclasses and Post Surgery Acute Inflammation: A Pilot Study - Yasmin Bains; Russell Caccavello; Kazuhiko Kotani; Alejandro Gugliucci (MDPI AG, 2019)
High density lipoproteins (HDL) structure and function studies are needed to better understand the heterogeneous nature of the HDL particle, and its interaction with associated proteins such as apolipoprotein A-1 (ApoA-1), paraoxonase 1 (PON1) and the environment. Our study assesses the effects of acute inflammation on PON1 and HDL subclasses in post-surgical colorectal cancer patients. PON1 was measured kinetically through its arylesterase and lactonase activity and HDL sub-classes were measured using Quantimetrix Lipoprint® System. White blood cells (WBC) counts, c-reactive protein (CRP) and serum amyloid A (SAA) levels were also analyzed using standard techniques. Our findings show that baseline PON1 activity is lower in colorectal cancer patients and significant reductions are observed in the acute inflammatory state post-surgery. PON1 changes are also inversely related to inflammatory markers such as SAA and CRP. In addition, our preliminary findings show that small and intermediate HDL decreases post-op Day 1. In conclusion, our study demonstrates the effects of chronic and acute inflammation on PON1. Specifically, PON1 arylesterase and lactonase activity is lower in states of chronic inflammation and further decreased in the acute inflammatory state. Additionally, in our limited sample size, while changes in PON1 and HDL subclasses may be variable in the acute inflammatory period, small HDL decreased with a loss of PON1 activity in the subacute phase.